Genomic insights and comparative analysis of Colletotrichum species associated with anthracnose fruit rot and crown rot of strawberry in North Carolina - Adhikari, Tika B.; Muzhinji, Norman; Philbrick, Ashley N.; Louws, Frank J. (Frontiers in Microbiology, 2025)
Colletotrichum is a large genus of fungal phytopathogens responsible for significant economic losses in numerous crops globally. These pathogens exhibit varying host specificities; some have a broad host range, while others are more limited. To explore the genetic composition and underlying factors of fungal virulence and pathogenicity, we sequenced the genomes of seven isolates of Colletotrichum spp.: three from the C. acutatum and four from the C. gloeosporioides. These isolates were sourced from anthracnose fruit rot and crown rot of strawberry in North Carolina. Phylogenetic and phylogenomic analyses classified the isolates within the C. acutatum as C. nymphaeae, while those in the C. gloeosporioides were identified as C. siamense. The genome sizes of the C. nymphaeae isolates ranged from 50.3 Mb to 50.7 Mb, with 14,235 to 14,260 predicted protein-coding gene models. In contrast, the genome sizes of the C. siamense isolates ranged from 55.7 Mb to 58.6 Mb, with predicted protein-coding gene models ranging from 17,420 to 17,729. The GC content across all genomes spanned from 51.9 to 53.7%. The predicted gene models included effectors (339 to 480), secondary metabolic gene clusters (67 to 90), and carbohydrate-active enzymes (800 to 1,060), with C. siamense isolates exhibiting the highest numbers in these categories. The genomic resources from this study will aid in resolving taxonomic challenges associated with Colletotrichum spp., elucidate their evolutionary history, and enhance the understanding of fungal biology and ecology, which is crucial for developing effective disease management strategies.